(untitled) (International Journal of Engineering and Computer Science, 2014)
Assessment is the basic fundamental activity of all learning environments. Therefore all learning management systems (LMS) provide the assessment facilities like (e.g., the formation, implementation, and valuation of multiple choice tests as well as programming assignments).This paper mainly elaborates the principles of service oriented paradigms, those are applicable for routine evaluation of programming assignments as well as multiple choice questions. The most prominent aspect of this assessment solution is, it can assess the programs written in any programming languages. Moreover, it can be easily interfaced with different existing learning management systems. This paper also presents the design of a flexible e-Assessment system based on the Design Methodology Management(DMM) technology which provides a framework for the system development.